Adhesive AuNP tape-mediated hierarchical assembly of multicenter DNA nanocomplexes for tumor cell nucleus-targeted staged drug delivery in vivo. (December 2022) - Li, Congcong; Gao, Yansha; Li, Qian; Luo, Shasha; Liao, Wenqiang; Wu, Zai-Sheng
Abstract: Developing DNA nanostructures as delivery vectors into organelles is a key technical barrier because of their innate poor pharmacokinetic properties. Herein, we propose a unique concept for high precision cancer therapy by using small gold nanoparticles (AuNPs) as adhesive nano-tapes to fold a long string of aptamer-attached tetrahedral DNA pearls (Apt-Nano-Tetra) into a spherical multicenter DNA nanostructure that can serve as a nucleus-targeted drug delivery carrier (Apt-ADMC) with a 75～85 times enhanced doxorubicin (Dox)-loading capacity. After specifically entering target tumor cells, Dox-Apt-ADMC is disassembled into individual AuNPs surrounded by short Apt-Nano-Tetra, finally reaching cell nucleus and causing cell apoptosis. Even if Dox-Apt-ADMC is treated with fetal bovine serum for 12 h, the drug delivery ability is not compromised, contributing to high functional stability in circulation system. As such, the systemically-administrated Dox-Apt-ADMC shows 7 times enhanced tumor accumulation and almost 100% inhibits tumor growth without detectable systemic toxicity. Graphical Abstract: ga1 Highlights: Developing DNA nanostructures as drug delivery vectors into organelles is a key technical barrier of drug delivery. We proposed a nucleus-targeted drug delivery carrier by folding a long string of tetrahedral pearls with gold nanoparticles. The nucleus-targeted drug delivery carrier has enhanced drug-loading capacity. Drug can be delivered to the nucleus by nucleus-targeted carriers and exert their therapeutic activity. The nucleus-targeted drug delivery carrier shows desirable tumor accumulation and tumor inhibition.